The impact of fertilization on the chicken egg yolk plasma and granule proteome 24 hours post-lay at room temperature: capitalizing on high-pH/low-pH reverse phase chromatography in conjunction with tandem mass tag (TMT) technology. Issue 7 (8th July 2015) - Padliya, Neerav D.; Qian, Meiqian; Mimi Roy, Sushmita; Chu, Patrick; Zheng, Haiyan; Tess, Alex; Dariani, Maghsoud; Hariri, Robert J.
<x xml:space="preserve">Abstract</x> Mass spectrometry-based proteomics may help develop egg yolk-based products optimized for specific applications.